PENGEMBANGAN MODUL BIMBINGAN PRIBADI SOSIAL BAGI GURU BIMBINGAN KONSELING UNTUK MENGHADAPI BENCANA ALAM - Ayriza, Yulia (Universitas Negeri Yogyakarta, 2009)
This study was aimed at developing module material for Guidance and Counseling teachers to increase the psychological preparedness of senior high school students in facing natural disasters. Using the research and development approach, the researcher involved 48 Guidance and Counseling teachers in the special region of Yogyakarta as research participants for needs assessment purposes. The modules were tried out to Guidance and Counseling teachers of senior high schools in the special region of Yogyakarta, involving 6 people at the initial field, 15 people at the main field, and 65 people at the operational field. Instruments applied to collect data were either opened or closed questionnaires. The collected data, the quantitative as well as the qualitative ones, were analyzed descriptively. Results obtained from this study are: (1) Material required by Guidance and Counseling teachers for module of psychological preparedness in facing natural disaster cover cognitive aspects ( 14,58%), affective aspects ( 31,25%) and psychomotoric aspects ( 52,08%); (2) The module of